Genome-Wide Differential Expression Profiling of Ovarian circRNAs Associated With Litter Size in Pigs - Xu, Gaoxiao; Zhang, Huifang; Li, Xiao; Hu, Jianhong; Yang, Gongshe; Sun, Shiduo (Frontiers in Genetics, 2019)
Circular RNAs (circRNAs) have been emerging as an important regulator in mammalian reproduction via acting as miRNA sponges. However, the circRNAs in porcine ovarian related with litter size remains largely unknown. In this study, porcine ovaries with smaller or larger litter size (SLS or LLS) were subjected to high-throughput RNA-sequencing. In total, 38,722 circRNAs were identified, of which 1,291 circRNAs were commonly expressed in all samples. There were 56 circRNAs significantly down-regulated and 54 circRNAs up-regulated in LLS pig (|log2 (Fold change) |>1, FDR < 0.05). Bioinformatics predicted that most of circRNAs harbored miRNA binding sites, and the expression patterns of circRNAs and their putative binding miRNAs were validated by qPCR. Moreover, the expression of circ-TCP11/miR-183 was significantly reversely correlated and their direct interaction was confirmed by dual-luciferase assay. Our study indicates that circRNAs may play potential effects on modulating porcine litter size.